2017
DOI: 10.1016/j.bmc.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anti-proliferative activity, SAR study, and preliminary in vivo toxicity study of substituted N,N′-bis(arylmethyl)benzimidazolium salts against a panel of non-small cell lung cancer cell lines

Abstract: A series of N,N′-bis(arylmethyl)benzimidazolium salts have been synthesized and evaluated for their in vitro anti-cancer activity against select non-small cell lung cancer cell lines to create a structure activity relationship profile. The results indicate that hydrophobic substituents on the salts increase the overall anti-proliferative activity. Our data confirms that naphthylmethyl substituents at the nitrogen atoms (N1(N3)) and highly lipophilic substituents at the carbon atoms (C2 and C5(C6)) can generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Authors attribute this to the release of silver. This further establishes the importance of the relationship between lipophilicity and cytotoxicity, as demonstrated in previous studies [ 95 , 96 , 97 , 98 ].…”
Section: Antitumor Activity Of N -Heterocyclic supporting
confidence: 87%
“…Authors attribute this to the release of silver. This further establishes the importance of the relationship between lipophilicity and cytotoxicity, as demonstrated in previous studies [ 95 , 96 , 97 , 98 ].…”
Section: Antitumor Activity Of N -Heterocyclic supporting
confidence: 87%
“…Although it has been shown that the quinolylmethyl substituent at the N 1 or N 3 position could be used to increase solubility and not severely alter anti-cancer activity, 11–13 the highest anti-cancer activities were observed with the most lipophilic compounds containing two naphthylmethyl substituents. Therefore, molecular excipients such as cyclodextrins (CD), which have been used to improve drug solubility and the bioavailability of such compounds, 14 were considered to aid in solubilizing highly lipophilic and highly active compounds.…”
mentioning
confidence: 99%
“…Therefore the aqueous solubility achieved by the substitution of imidazolium salts with a TPP moiety was desirable. The biscationic nature of TPP1 has considerably enhanced the water solubility to 8 mg/mL as compared to previously reported systems such as starting material 1, which has a solubility of <1 mg/mL [46]. While the aqueous solubility is helpful for aiding in the process of TPP1 delivery, it is important to balance that with sufficient lipophilicity to diffuse across the cell membrane.…”
Section: Synthesis and Characterizationmentioning
confidence: 94%
“…The synthesis outlined in Scheme 1 shows the synthetic strategy used to produce the triphenylphosphonium (TPP)-substituted benzimidazolium salt (TPP1). 2-(3hydroxypropyl)-1,3-bis(naphthalen-2-ylmethyl)benzimidazolium bromide (1) was synthesized, using a previously published procedure [46]. To transform the alcohol to a TPP substituent, compound 1 was reacted with thionyl bromide to form the alkyl halide.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation